Market misreaction? Leverage and mergers and acquisitions - C. N. V. Krishnan; Vasiliy Yakimenko (Journal of Risk and Financial Management, 2022)
Using a large database of U.S. mergers and acquisitions (M&As) announced from 2010 through 2017, we examine the effects of capital ratio (leverage) on the announcement period stock price reaction as well as on longer-term stock returns and performance, for banks, making comparisons with non-banks. We compare announcement period reactions (computed in different ways) for lower (lower than sample median) capitalized banks and non-banks with that for higher capitalized banks and non-banks. We confirm our results using multivariate analyses-after controlling for year and industry fixed effects-and we check the associations of capital ratio with announcement period abnormal returns, longer-term performance, as well as certain bank-specific and non-bank specific performance measures. For banks, we find that a lower capital ratio of acquirers at the time of the announcement of the M&A is significantly associated with negative announcement period abnormal returns. However, for these banks, the longer-run abnormal returns and performance are positive. The opposite is true for non-bank M&A announcements: higher equity ratios (lower leverage) of acquirers as at the time of the announcement is significantly associated with negative announcement period abnormal returns. Yet, for such non-banks, the longer-run abnormal returns and performance are positive. This shows that the market may misreact, on average, to both bank and non-bank M&A announcements based on the acquirer's leverage at the time of the announcement.
Keywords: G34; 330; mergers and acquisitions; M&A; acquirer leverage; capital ratio; equity ratio; bank M&As; non-bank M&As; announcement period returns; post-announcement returns; post M&A performance